ERISA's Curious Coverage - Peter J. Wiedenbeck (Washington University Law Quarterly, 1998)
The regulation of employee benefits entails a delicate balance—measures intended to improve the quality of health insurance or retirement programs, if taken too far, deter some employers from providing such benefits at all. Because the availability of benefits depends on employer decisionmaking, ERISA necessarily incorporates cost containment and the preservation of employer flexibility. This article examines the fit between ERISA’s policy goals and existing interpretations of ERISA's reach. It shows that although the statute's anti-abuse and protective policies have been influential in defining the scope and extent of benefit plan regulation, neither is pursued with single-minded consistency. In the main, this inconsistency is traceable to historical circumstance rather than reasoned compromise between competing objectives.
Keywords: Employee fringe benefits; Federal preemption (Labor law); Fiduciary duties; Retirement income; Employee Retirement Income Security Act of 1974